Effects of geographical origin, variety and farming system on the chemical markers and in vitro antioxidant capacity of Brazilian purple grape juices. (April 2016) - Margraf, Tiago; Santos, Érica Neulyana Taborda; de Andrade, Eriel Forville; van Ruth, Saskia M.; Granato, Daniel
Abstract: The effects of farming system, geographical origin, and grape variety on the in vitro antioxidant capacity, some physicochemical properties and chemical composition were investigated. Major and minor phenolic compounds, reducing and antioxidant assays using chemical and biological systems were determined in n = 62 100% purple grape Brazilian juices ( Vitis labrusca L.) from organic and conventional systems from the three largest producing regions. Results were subjected to ANOVA, MANOVA, and principal component analysis. No distinction was observed between organic and conventional grape juices regarding the in vitro antioxidant/reducing capacities, but only through the analysis of individual phenolic acids. The geographical origin and grape variety played a more important role in distinguishing Brazilian grape juices according to the antioxidant activity and some chemical markers. MANOVA was applied and the combined effect of farming system and geographical origin was only significant for tonality (p = 0.044) and protocatechuic acid content (p = 0.030). Correlation analysis was performed and results showed that total phenolic content, total flavonoids, flavonols, anthocyanins, and condensed tannins were statistically associated (p < 0.05) with FRAP, ABTS, and reducing potential of the hydrophilic phenolic compounds (RPHPC). Ascorbic acid did not seem to be involved in the antioxidant potential of the selected purple grape juices. Protocatechuic acid was statistically correlated to FRAP (r = 0.4636, p < 0.001), ABTS (r = 0.3298, p = 0.010), and RPHPC (r = 0.3623, p = 0.004), while ferulic acid correlated with FRAP (r = 0.3410, p = 0.008) and RPHPC (r = 0.2662, p = 0.040). The inhibition of lipid peroxidation conducted at 37 °C in a biological system buffered at pH 7.4 was significantly (p < 0.05) correlated to RPHPC (r = 0.533, p = 0.013) and to the scavenging activity toward ABTS radical (r = 0.505, p = 0.020). In addition, principal component analysis revealed that the inhibition of lipid peroxidation was associated with higher contents of total phenolic content, flavonoids, anthocyanins, flavonols, condensed tannins, and protocatechuic acid. Additionally, both spectrophotometric and chromatographic data regarding the phenolic composition seemed to be suitable approaches to differentiate Brazilian organic and conventionally-produced purple grape juices using PLS-DA as the classification efficiency in the calibration and validation steps were 78% and 75%, respectively. Graphical abstract: Highlights: Organic (O) and conventional (C) purple grape juices were analyzed for chemical composition and antioxidant activity (AA). Syringic and p -coumaric acids levels were different between O and C juices. Differences in AA were observed of juices from distinct origins. Bordo grape juice presented the highest content of phenolic compounds and AA. The inhibition of lipid peroxidation was correlated to the AA measured by chemical methods.